A pooled long-term follow-up after radiotherapy for prostate cancer with and without a rectal hydrogel spacer: impact of hydrogel on decline in sexual quality of life - Seymour, Zachary A.; Pinkawa, Michael; Daignault-Newton, Stephanie; Bosch, Walter; Michalski, Jeff M.; Gay, Hiram; Hamstra, Daniel A. (Frontiers in Oncology, 2023)
To analyze the impact of prostate rectal spacers on sexual quality of life (QOL) following external beam radiation therapy (RT).Patient reported QOL was evaluated using the Expanded Prostate Cancer Index Composite (EPIC).Patients were pooled from two sources: a randomized controlled trial and a non-randomized cohort of patients from a single institution. Both cohorts used the same spacing product and QOL instrument.Analysis was limited to those with good baseline pre-treatment sexual QOL (EPIC >/=60). Differences in QOL summary score as well as individual items were assessed compared to baseline and between treatment arms.A total of 128 men had good baseline sexual function and were evaluated (64% with spacer and 36% without) with QOL data available for median 33-months (range: 2.5-69.4 months). Men without spacer were more likely to have declines in sexual function (p<0.0001), bother (p=0.0002), and sexual summary score (p<0.0001). A minimally important difference of 10-points (1xMID) and 20-point (2xMID) were more likely without rectal spacer (10-point: Odds Ratio 3.53, (95% confidence interval 1.11-11.2), p=0.032; 20-point: Odds Ratio 3.29, (95% confidence interval 1.16-9.33), p=0.025).Seven of 13 QOL items were statistically superior with hydrogel (6/9 functional and 1/4 bother) while no items were statistically superior for control. At baseline more men treated with hydrogel had erections sufficient for intercourse; however, when analyzed only by the men with best baseline erectile potential and excluding those with worse function the benefit of rectal spacing was maintained with a higher likelihood of preservation of erections sufficient for intercourse in those treated with hydrogel. In this pooled analysis of QOL after prostate RT, utilization of a hydrogel spacer was associated with better sexual QOL, less men with measurable declines in sexual QOL, and higher rates of adequate erectile function.